Spatial analysis, geospatial data and land-change models for modelling agricultural land changes - Viana, Cláudia (2022)
At the core of global initiatives, several relevant adaptive management and policy approaches are being discussed and redirected towards achieving global food production objectives and food security for the present and future generations. In particular, agricultural land systems are the principal biogeophysical source to ensure food security and nutritional benefits. However, agricultural land systems change over time, indirectly influencing global food production and food security. Thus, in the coming decades, agricultural land systems will face complex challenges (e.g., the changing of food consumption pattern, climate change, land abandonment and/or intensification); the extent to which they will be able to support the security of the global food system will be determined by their efficiency, sustainability, and equitability. With the integration of spatial analysis, geospatial data and land-change models, there is a practical opportunity for modelling agricultural land systems. This, in turn, can provide meaningful information to assist decision-making processes, anticipate future changes, and design robust strategies in the long term to manage impending challenges.